Effect of milling methods on the properties of rice flour and gluten-free rice bread. (July 2019) - Wu, Tong; Wang, Lili; Li, Yan; Qian, Haifeng; Liu, Liya; Tong, Litao; Zhou, Xianrong; Wang, Li; Zhou, Sumei
Abstract: The properties of rice flour are very important for making gluten-free rice bread. In this study, rice flour was prepared using different milling methods (wet-milling, cyclone-milling and ultrafine-milling) to investigate their effect on the properties of gluten-free rice bread. The milling method was found to significantly affect the damaged starch content, state of the starch granule, gelatinization temperature and absorption enthalpy of rice flour (p < 0.05). The starch granules of flour prepared by wet milling had a high integrity, low damaged starch content (2.80 g/100 g), high gelatinization temperature, and high values of absorption enthalpy and gel strength compared to ultrafine-milling and cyclone-milling methods. As the deformation of the starch in the rice grains decreased, the amount of completely gelatinized starch granules in the bread decreased, with its specific volume also decreasing from 3.1 to 1.2 mL/g. Increase in starch damage content was observed to decrease the specific volume of bread, consequently increasing the hardness of bread. Also, uneven pores were observed, and the number and size of internal pores decreased. This indicated that wet-milled rice flour with a low content of damaged starch and higher starch granules integrity produced better gluten-free rice bread. Highlights: Damaged starch content has a significant effect on rice bread. Wet milled flour has lower damaged starch content and more intact starch granules. Compared with ultrafine and cyclone, wet-flour is more suitable for making bread. Rice flour with low damaged starch content is a good material for making rice bread. Starch granules that are not fully gelatinized in baking may help form texture.